PENGUJIAN EKSTRAK DAUN KECOMBRANG (Nicolaia speciose Horan) SEBAGAI PENCEGAH PERTUMBUHAN JAMUR Saprolegnia sp. PADA IKAN GURAMI (Osphronemus gouramy) SECARA IN VITRO - Horas M. C. Simatupang; Yunasfi Djayus; Dwi Suryanto (AQUACOASTMARINE, 2018)
Kecombrang have chemical content such as saponins, flavonoids, polyphenols, essential oils, and saponins which maypotencial as antimicroba. The purpose of this study was to determine the optimal concentration of kecombrang (Nicolaia speciosa) leaf extract to inhibit the growth of fish pathogenic fungi Saprolegnia sp. in gourami (Osphronemus gouramy). This research was conducted 3 months, from January to April 2017. Methanol, ethyl acetate and n - hexane were used as solvents for kecombrang leaf extraction. Assay on inhibitory of extract of kecombrang to Saprolegnia sp. used extract concentration of 0, 20, 40, and 60. Toxicity test (LC50) was conducted in gouramy at extract concentration of 1000, 100, 10, and 0 ppm. Water quality was observed icluding temperatute, DO, pH. The results showed that kecombrang leaf extract was reddish green, reddish brown, and yellowish green in color. Preliminary test of phytochemical compound of the extract showed that the extract contained saponins, tannins, and terpenes. The inhibitory test showed that ethyl acetate at concentration of 60% was able to inhibit up to 7.7 cm of the fungal growth. LC50 of methanol, ethylacetat, and n - hexane leaf extract was 25.4, 22.7, and 26.2 ppm, respectively. Temperature was 29 - 30 0C, DO was 7.0 - 7.2, and pH was 7.4 - 7.5 at the time of study.Keywords: inhibitory test, kecombrang, leaf extract, gouramy (Osphronemus gouramy), saponin, Saprolegnia sp.